The Fenomenal World in magical Realism according to Wendy B. Faris in Novel “Das Parfum” by Patrick Süskind - Sugiarti, Yati; Malia, Lia; Sahayu, Wening; Setiawan, Akbar Kuntardi (Future Science)
The aim of this study is to discuss the phenomenal world in magical realism according to Wendy B. Faris in the novel “Das Parfum” by Patrick Süskind. The phenomenal world is the presence of phenomenal world whose objects, places, figures, time and events in narrative texts have the characteristics of magical realism. It is explicitly and convincingly described in the story, but it does exist in reality. The phenomenal places in both the investigative novel and in reality describe phenomenal objects and phenomenal events. The phenomenal characters and time cannot be found in this novel.